2018
DOI: 10.1111/dom.13586
|View full text |Cite
|
Sign up to set email alerts
|

Urinary glucose excretion after dapagliflozin treatment: An exposure‐response modelling comparison between Japanese and non‐Japanese patients diagnosed with type 1 diabetes mellitus

Abstract: Aims To assess the dapagliflozin exposure‐response relationship in Japanese and non‐Japanese patients with type 1 diabetes mellitus (T1DM) and investigate if a dose adjustment is required in Japanese patients. Materials and Methods Data from two clinical studies were used to develop a non‐linear mixed effects model describing the relationship between dapagliflozin exposure (area under the concentration curve) and response (24‐hour urinary glucose excretion [UGE]) in Japanese and non‐Japanese patients with T1DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…The identified covariates, baseline eGFR and 24‐hour median blood glucose had significant impact on dapagliflozin efficacy (as measured by UGE) in both studies. This is consistent with the previously developed PK/PD model for T1DM in adults, where baseline eGFR and 24‐hour median blood glucose were found to affect dapagliflozin E max and AUC24 50 …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The identified covariates, baseline eGFR and 24‐hour median blood glucose had significant impact on dapagliflozin efficacy (as measured by UGE) in both studies. This is consistent with the previously developed PK/PD model for T1DM in adults, where baseline eGFR and 24‐hour median blood glucose were found to affect dapagliflozin E max and AUC24 50 …”
Section: Discussionsupporting
confidence: 91%
“…For example, Sokolov et al . reported that blood glucose was the most influential covariate on dapagliflozin UGE efficacy in adult patients with T1DM while fasting plasma glucose had a larger impact on dapagliflozin efficacy than renal function in adult and paediatric patients with T2DM …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of insulin dose reduction on SGLT2 inhibitor efficacy has been previously described in terms of urinary glucose excretion, where T1DM patients who had greater total insulin dose reduction were also observed to have a more pronounced urinary glucose excretion response. 28,29 It is unclear why a similar covariate effect was not identified in the current analysis.…”
Section: Discussionmentioning
confidence: 70%
“…28,29 It is unclear why a similar covariate effect was not identified in the current analysis. The impact of insulin dose reduction on SGLT2 inhibitor efficacy has been previously described in terms of urinary glucose excretion, where T1DM patients who had greater total insulin dose reduction were also observed to have a more pronounced urinary glucose excretion response.…”
Section: Exposure-response Modelmentioning
confidence: 70%